A geographical survey of Africa : its rivers, lakes, mountains, productions, states, populations, &c. with a map of an entirely new construction, to which is prefixed a letter to Lord John Russell regarding the slave trade and the improvement of Africa - MacQueen, James, 1778-1870 (Cass library of African studies. Travels and narratives A geographical survey of Africa, 2013)
The owner of West Indian plantations, McQueen collected extensive information from slaves which led him correctly to the conclusion that the Niger ended in the great delta of the Blight of Benin. First published in 1840.